Between the Violence and the Citizenship: A Glance on the Youth Mortality - Medeiros, Thaís Juliana; Serrata Malfitano, Ana Paula (O Mundo da Saúde, 2015)
The thematic of the violence and its association with the youth has been not only an academic concern but also social policies, with deployments in the Public Health area. This paper aims to discuss the youth mortality by homicides and suicides in a medium-sized city, São Carlos, SP, in the last decade. In terms of methodology, it is applied the discussion about the database, based on the citizenship concept. In this sense, official data about local mortality were collected in the Centro de Informações sobre a Saúde (CIS), São Carlos, limited to young people deaths from ages between 15 to 29 years old and between 2000 to 2010 years, identifying gender, race and social class. The results show that the majority of the homicides and suicides happened with young men and African descendant from the poorest city’s neighborhoods. It is discussed the citizenship dimension of the poor and the black young living in the disadvantaged areas, showing that the youth death is related to the lack of access to rights and citizenship. It is urgent to address the issues of social inequality to discuss effectively the life disruption of a group of young people in Brazil.